The genotype of Aujeszky's disease viruses isolated in Argentina - Echeverría, María Gabriela (1994)
Genomes of four Argentine isolates of Aujeszky's disease virus (ADV) (Rio Cuarto/79, Mercedes, Chanar Ladeado-7 and Chanar Ladeado-15) from pigs were characterized and compared with four ADV strains obtained from U.S.A. (Indiana-S), Sweden (Sweden 66), France (Alfort) and Japan (Yamagata-S81) by restriction endonuclbase (RE) analysis. Although three Argentine isolates were classified into type I of BamHI cleavage pattern, one isolate, Mercedes, belonged to type II, according to the classification by Herrmann et al. [6]. Since this type II virus was first isolated in 1981, no outbreak of ADV infection by this type has so far been reported in Argentina. This may imply that the immediate measures by total slaughter of pigs in the farm led successful eradication of the type II ADV infection in Argentina. This report is the first epidemiological study using RE analysis on ADV strains in this country.